The powerful world of antisense oligonucleotides: From bench to bedside. (31st March 2020) - Quemener, Anaïs M.; Bachelot, Laura; Forestier, Anne; Donnou‐Fournet, Emmanuelle; Gilot, David; Galibert, Marie‐Dominique
Abstract: Antisense oligonucleotides (ASOs) represent a new and highly promising class of drugs for personalized medicine. In the last decade, major chemical developments and improvements of the backbone structure of ASOs have transformed them into true approved and commercialized drugs. ASOs target both DNA and RNA, including pre‐mRNA, mRNA, and ncRDA, based on sequence complementary. They are designed to be specific for each identified molecular and genetic alteration to restore a normal, physiological situation. Thus, the characterization of the underpinning mechanisms and alterations that sustain pathology is critical for accurate ASO‐design. ASOs can be used to cure both rare and common diseases, such as orphan genetic alterations and cancer. Through pioneering examples, this review shows the versatility of the mechanisms of action that provide ASOs with the potential capacity to achieve custom treatment, revolutionizing personalized medicine. This article is categorized under: RNA in Disease and Development > RNA in Disease RNA Interactions with Proteins and Other Molecules > Small Molecule–RNA Interactions Abstract : ASO functioning towards personalized medicine.